Central Nervous System Xanthoma Disseminatum: Response to 2CdA in an Adolescent. (22nd July 2022) - DeMoss, Patrick; Tang, Nancy; Yeom, Kristen; Chiang, Audris; Marqueling, Ann L.; Jeng, Michael R.
Abstract : Xanthoma disseminatum is a normolipemic non-Langerhans cell histiocytosis characterized by red-brown rubbery papules of the skin which coalesce into plaque-like lesions with symmetric involvement of face, flexor, and intertriginous areas. Less commonly, xanthoma disseminatum may affect mucosal linings, abdominal organs, and the central nervous system, leading to endocrinopathies. We report a 12-year-old adolescent with mucosal, central nervous system, and painful cutaneous lesions, further complicated by diabetes insipidus and amenorrhea. Treatment with 2-chlorodeoxyadenosine led to relief of pain and significant improvement of mucosal, central nervous system, and cutaneous lesions, with subsequent restoration of menstrual cycles.